Oral Changes after Radiotherapy in Patients with Head and Neck Cancer - Maldonado, Natalia Souto Outeda; Prosdocimi, Fabio C.; Sampaio, Rui Manuel Freire; Junior, Adhmar Sani; Schmidt, Arthur Georg; Roman-Torres, Caio Vinicius G. (Journal of Medical Biomedical and Applied Sciences, 2018)
Cancer of the mouth begins in the oral cavity which includes: lips, jugal mucosa, teeth, gums, the first two-thirds of the tongue, floor of mouth, hard palate and retromolar trigone. Radiation therapy is a method capable of destroying tumor cells, employing a beam of ionizing radiation, seeking to eradicate all tumor cells with the least possible damage to the surrounding healthy cells at the expense of which the regenerated area will be regenerated. The objective of the present literature review was to report the main pathologies related to the performance of radiotherapy in patients with head and neck cancer. We selected articles published in the years from 1978 to 2017. The response of the tissues to radiation depends on several factors, such as the sensitivity of the tumor to radiation, its location and oxygenation, as well as the quality and quantity of radiation, in addition to the total time given. The oral complications of radiotherapy of head and neck neoplasms are common because they are rapidly renewing cells suffering greater action of the radiation agents, and can compromise the quality of life of the patient, besides negatively affecting the course of the cancer treatment until its suspension. Adverse reactions to radiation therapy are classified as acute, which occur during treatment or up to three months after the end, and late, which may manifest several months or years after the end of treatment. Oral mucositis is a clinically important and sometimes dose-limiting complication of cancer therapy. Mucositis lesions can be painful, affect nutrition and quality of life, and have a significant economic impact. Protocols for the treatment of the adverse effects of radiotherapy in the stomatognathic system are the responsibility of the dental surgeon. These include symptomatic relief, systemic medicines, physiotherapy, accumulating and oral lubricants, excellent oral hygiene and diet of certain types of food.